PENENTUAN JUMLAH TENAGA KERJA BERDASARKAN WAKTU STANDAR DENGAN METODE WORK SAMPLING - Zulbaidah Zulbaidah; Abdul Malik Ali; Fitriadi Fitriadi (Jurnal Optimalisasi, 2015)
Brick molding company has been very flourishing in Nagan Raya, but in this study focuses on molding bricks located at the Blang Bintang, Simpang Maklina, Gampong Cot Beetle, district. Kuala, Nagan Raya. Problems that occur in this company include: determining the standard time work, measuring work time using work sampling method, measuring the working time, calculating standard labor. This study aims to measure the standard time by determining the amount of labor. This research work sampling method. This conduct by direct observation activities of operators in completing the work which is then used to measure the labor force. Standard time operator workload and hours of productive work in completing the work, so that can know the amount of labor that should be employed. The analysis results obtained in this study .2350 minute of normal time, standard time of 0.2355 min, whereas the number of personnel is 0.0532. It can be concluded that the normal time as much as 5.32% so that idle time is still too big.Key Words: Standard Time , Work Sampling , Workload, Labor.